The development of rapid method for detection of ethanol in mouthwash using E-Nose - Octavianti, Fitri; Jaswir, Irwandi; Akmeliawati, Rini; Rahmadsyah, Adi; Abdul Aziz, Azrul Hafiz; Abdul Rahman, Russly (Springer Nature Singapore Pte Ltd., 2019)
The purpose of this study is to check for ethanol (EtOH) content in mouthwash products sold in Malaysia market using portable electronic-nose (E-Nose). For this study, 20 mouthwashes were tested with nine of the samples contain EtOH as part of its ingredients. The problem with those products is that it does not disclose the concentration of the EtOH as part of its labelling. This is important since long-term use of ethanol-containing mouthwash may result in adverse health effect to the consumer. The process parameters used in this study was optimized using Response Surface Methodology (RSM), with strong relations between actual and predicted sensor response yield correlation of determination, R2 of 0.9756. Optimum process parameters generated by Design Expert 7.1.5 showed that the optimum volume for EtOH sample was 5.84 mL for 1.45 min time of detection. While for screening process, it was found that from the detection of alcohol-free mouthwash using portable E-Nose, no alcohol content detected with ‘alcohol free’ was displayed on the LCD screen of the device. However, 9 out of 10 mouthwash samples that have no ‘alcohol free’ label on the products contain more than 10% (v/v) EtOH. Hence, this study had successfully optimized the process parameters and screened the mouthwashes sold in Malaysia market for the presence of EtOH.